FUZZY LOGIC APPARATUS AS A TOOL FOR ASSESSING THE EFFECTIVENESS OF DIGITALIZATION OF A COMPANY - V. S. Kokhanova (Вестник университета)
In this article, the author gives an example of using the apparatus of fuzzy logic in assessing the effectiveness of digitalization of an enterprise, specifies indicators that can be used as criteria for building a system for assessing the effectiveness of digitalization, as well as provides an overview of existing developments. Within the framework of the article, the study outlines the directions of modification of classical estimation methods that are possible using the apparatus of fuzzy logic. The paper substantiates the choice of a universal fuzzy logic tool as a mathematical apparatus for forming an assessment: a system of fuzzy logical conclusions – standard five-level [0; 1]-classifiers. The possibility of fuzzy classification of properties, as well as qualimetry based on the aggregation of hierarchies of factors, will make it possible to assess the level of efficiency of enterprise digitalization by the degree of success.